2022
DOI: 10.1088/1755-1315/1053/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Vertical accuracy comparison of multi-source Digital Elevation Model (DEM) with Airborne Light Detection and Ranging (LiDAR)

Abstract: Digital Elevation Model (DEM) is a digital representation of ground surface topography or terrain. There are many freely available DEM data with a spatial resolution of 30 m to 90 m. Nevertheless, their vertical accuracy may vary, depending on the vegetation cover and terrain characteristics. This study examined the vertical accuracy of open-access global DEMs (ALOS PALSAR, ASTER GDEM3, SRTM, TanDEM-X) and fused DEM (EarthEnv-DEM90, MERIT DEM). Their performances were assessed using a Digital Terrain Model (DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Similarly, MERIT Hydro -a global flow direction map at 3-arc seconds was conceptualized and developed by Yamazaki et al [14] by considering MERIT DEM and water body data sets. It is appreciated by the researchers due to its improved accuracy compared to other open-access DEMs by researchers like Uuemaa et al [4] and Chai et al [78]. However, its spatial resolution may be a limitation for regional-level applications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MERIT Hydro -a global flow direction map at 3-arc seconds was conceptualized and developed by Yamazaki et al [14] by considering MERIT DEM and water body data sets. It is appreciated by the researchers due to its improved accuracy compared to other open-access DEMs by researchers like Uuemaa et al [4] and Chai et al [78]. However, its spatial resolution may be a limitation for regional-level applications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown this DSM has one of the best vertical accuracies of global open-source elevation data, especially in open non-forested landscapes (e.g. Ferreira, Cabral, 2021;Chai et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Moiret-Guigand, 2021). Equator) covering land area from 90 N to 60 S, selected for its ability to clearly represent landscapes such as river networks and hill-valley structures even in flat areas where height errors could be larger than topography variability (Yamazaki et al, 2017;Bhardwaj, 2021;Chai et al, 2022). It is derived from seven different opensource datasets, delivered as 57 GeoTiff files 30º by 30º region each, at ~90 m resolution (in total 90.0 GB), representative of the year 2018.…”
Section: Reference Data and Overall Methodologymentioning
confidence: 99%